2015
DOI: 10.5601/jelem.2015.20.2.845
|View full text |Cite
|
Sign up to set email alerts
|

Content of some nutrients in Scots pine, silver birch and Norway maple in an urbanized environment

Abstract: In the late 18 th and early 19 th c., a drastic reduction in the area of forests due to their excessive exploitation occurred in Europe, which gave rise to the birth of afforestation efforts. The chemical composition of plants, including trees, depends on the many biotic and abiotic environmental factors. The aim of this study was to determine the content of some nutrients in needles and bark of Scots pine (Pinus sylvestris L.), leaves and bark of silver birch (Betula pendula) and Norway maple (Acer platanoide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The foliar Na concentration of Pc reached up to six-fold the control concentration (some 930 mg kg −1 DM) nonetheless Modrzewska et al (2016) reported foliar Na concentrations up to 264 mg kg −1 DM for B. pendula growing alongside roads with heavy traffic exposed to salt for winter. Leaves of Pc plants accumulated the highest amount of Mn, P, and Na, whereas they accumulated lower amounts of Cr, Mg, and Ca, confirming what was stated above.…”
Section: Discussionmentioning
confidence: 88%
“…The foliar Na concentration of Pc reached up to six-fold the control concentration (some 930 mg kg −1 DM) nonetheless Modrzewska et al (2016) reported foliar Na concentrations up to 264 mg kg −1 DM for B. pendula growing alongside roads with heavy traffic exposed to salt for winter. Leaves of Pc plants accumulated the highest amount of Mn, P, and Na, whereas they accumulated lower amounts of Cr, Mg, and Ca, confirming what was stated above.…”
Section: Discussionmentioning
confidence: 88%